Colorimetric Determination of Meprobamate after a simple derivatization - Sabir, Noor-alhuda A.; Al-Janabi, Khalid Waleed S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
A sensitive and environmentally benign spectrometric method was developed for quantifying Meprobamate (MEP). The analyzed MEP was derivatized into a colored complex and determined spectrometrically. The colorimetric analytical parameters were optimized and validated. Low limit of detection (LOD) was achieved down to 1.88Ã—10-6 mol/l while the limit of quantification (LOQ) was extended over the range of 1.97Ã—10-6 - 1.35Ã—10-3 mol/l. The high precision has been denoted by the 1.54% value of the coefficient of variation. The recovery was 96.07%, while the RSD (n=3) was 1.05 - 1.19%. The apparent molar absorptivity (Æ) obtained within 1154.7 - 1691.9 L.mol-1.cm-1. The outcomes have signified the high sensitivity of the technique. Furthermore, the avoidance of any traditional sample preparation steps prior to the analysis make the method an excellent environmental approach. There were no analytical interferences with the common composites. The method has been successfully verified for the quantification of MEP content in bulk pharmaceutical matrix and can be applied to determine other environmentally toxic carbamates.